THE EFFECTIVENESS OF ACTING PLAY SCRIPT TECHNIQUE TOWARDS STUDENTS’ SPEAKING ABILITY AT TENTH YEAR OF SMAN I LAMBUYA - Umar Umar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study investigated The Effectiveness Of Acting Play Script Technique towards Students’ Speaking Ability At Tenth Year Of SMAN I Lambuya. The research question of this study adressed “Does the Acting Play Script Technique have significant effect towards students’ speaking ability?". The objective of this study was to find out wether there is or not a significant effect of Acting Play Script (APS) tecnique towards student speaking at tenth year of SMAN I Lambuya. The hypothesis of this study was: H1 = If there is a significant effect of Acting Play Script technique towards students’ speaking ability at tenth year of SMAN I Lambuya, H0= If there is not a significant effect of Acting Play Script technique towards students’ speaking ability at tenth year of SMAN I Lambuya. This study is an experimental design by using one class that was given pre and post- tests. The design of this study was quasi experiment, meaning that there was only a group to be the subject in this study. The population of this study was all of the grade X students at SMAN Negeri 1 Lambuya who were registered in academic year 2018/2019 which consist of 5 classes. The sample of this study is 26 students. This sample was taken by using purposive sampling. The instrument of this study is a Speaking test, For making data in this research valid and more rejuvenate researcher was giving students’ first test before treatment in speaking and the last test after given treatment with Acting Play Script. The data of this study was analyzed by using descriptive statistics and inferential statistics. The finding shows that there is a significant effect of Acting Play Script technique towards students’ speaking ability at tenth year of SMAN I Lambuya. It can be seen that t count 11.56 > t table 2,050 at the significant level 0,05 and df 25. Therefore hypothesis of this study was accepted. It means that teaching of Acting Play Script technique was effective to improve students’ speaking ability at tenth year of SMAN I Lambuya.